Cyber security and operations management for Industry 4.0 - Elngar, Ahmed A.; Thillaiarasu, N; Elhoseny, Mohamed; Sagayam, K. Martin 1987- (CRC Press, 2023)
"Cyber Security and Operations Management for Industry 4.0 covers cyber security risks involved in the integration of Industry 4.0 into businesses and highlights the issues and solutions. The book offers the latest theoretical and practical research in the management of cyber security issues common in Industry 4.0 and also discusses the ethical and legal perspectives of incorporating cyber security techniques and applications into the day-to-day function of an organization. Industrial management topics related to Smart Factories, Operations Research, and Value Chain are also discussed"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on January 31, 2023)
Keywords: Computer security -- Management; Industry 4.0; Sécurité informatique; Gestion; Industrie 4.0; COMPUTERS / Cryptography; BUSINESS & ECONOMICS / Production & Operations Management; TECHNOLOGY / Operations Research; Computer security; Management